Do Excessive Wage Increases Raise Imports? Theory and Evidence - Jim Malley; Thomas Moutos (Center for Economic Studies and ifo Institute (CESifo), 2001)
This paper uses a model of trade in vertically differentiated products to examine the effects of excessive wage increases (i.e. above productivity) on the volume of commodity imports. The model predicts that for commodities, in which the country has comparative advantage in high quality varieties, an increase in excessive wages may result in a decrease in the volume of imports. The empirical validity of the model's predictions is demonstrated with the use of disaggregated Japanese import data for the period 1967-95. We also find that the aggregate volume of Japanese imports is not responsive to excessive wage changes.
Keywords: 330